Correlation between chromosomal distribution and embryonic findings on ultrasound in early pregnancy loss after IVF-embryo transfer - Ouyang, Yan; Tan, Yueqiu; Yi, Yan; Gong, Fei; Lin, Ge; Li, Xihong; Lu, Guangxiu (Human reproduction (Oxford), 2016)
Abstract STUDY QUESTION Do early pregnancy losses (EPLs) with and without embryos differ in chromosomal distributions? SUMMARY ANSWER The chromosomal abnormality rate is significantly higher in miscarriages with embryos than without after in vitro fertilization (IVF)-embryo transfer. WHAT IS KNOWN ALREADY Chromosomal abnormalities are the main causes of EPLs, the rate of which is up to 24–30% in the IVF population. Little research has been conducted on the correlations between the chromosomal distributions of EPL and the existence of an embryo or with the postmortem embryonic pole length, and the existing results have been inconsistent. STUDY DESIGN, SIZE, DURATION The data of 2172 women who underwent dilation and curettage (D&C) from January 2008 to December 2013 for missed abortion were analyzed retrospectively. The existence of an embryonic pole and the length of the postmortem embryonic pole of the EPL were evaluated by transvaginal sonography (TVS). Ultrasound findings were compared with karyotype results. PARTICIPANTS/MATERIALS, SETTING, METHOD This analysis included 2172 infertility patients who had singleton pregnancies and experienced EPLs after IVF-embryo transfer. The EPLs were divided into embryonic and anembryonic groups based on TVS diagnosis. The crown–rump length of the fetal pole (observed once) was measured twice for each fetus after confirmation of fetal death, subject to the final measurement before D&C. The karyotype analysis was performed using comparative genomic hybridization (CGH) plus fluorescence in situ hybridization technology. MAIN RESULTS AND THE ROLE OF CHANCE The chromosomal abnormality rate was significantly higher in male miscarriages with an embryo than in those without an embryo (54.14% versus 37.50%, P ≤ 0.001). In the anembryonic group, the abnormal karyotype rate was significantly higher in the yolk sac only than that in the empty sac group (46.11% versus 29.77%, P = 0.001); in the embryonic group, the abnormal karyotype rate in miscarriages with postmortem embryonic pole length >20 mm was significantly lower than that in miscarriages with pole length <10 mm (P = 0.006) and 10–20 mm (P = 0.036). There were significant differences in abnormal karyotype rates among miscarriages of different developmental stages (P ≤ 0.001). The cases with embryonic stages had the highest risk (54.89%) of an abnormal karyotype and those with fetal stages had the lowest risk (18.18%). There were significant differences in the length of postmortem embryonic poles among groups with different karyotypes (P ≤ 0.001). In addition, trisomy 21, monosomy X and triploidy had the longest lengths of postmortem embryonic poles (16, 15.3 and 11.6 mm, respectively). LIMITATIONS, REASONS FOR CAUTION Although the efficacy of a non-parametric test is less than that of a parametric test, non-parametric testing was used to compare the embryonic pole lengths in this study, owing to the non-normal distribution and non-homogeneous variances caused by limited cases of some rare chromosomal abnormalities. Another limitation was that CGH was unable to detect mosaicism. Furthermore, the results were not compared with a non-IVF population. Finally, maternal cell contamination is a major problem in studying miscarriage tissue, even using molecular techniques. WIDER IMPLICATIONS OF THE FINDINGS Although TVS findings clearly cannot replace karyotype information, our results are important because they call attention to the fact that EPLs that occur after implantation but prior to embryo formation frequently have normal karyotypes. This finding might direct future research towards studies of DNA sequences, or of epigenetic correlations with pregnancy failure. STUDY FUNDING/COMPETING INTEREST(S) This study was funded by the Scientific Research Foundation of Reproductive and Genetic Hospital of Citic-Xiangya. The authors have declared that no conflicts of interest exist. TRIAL REGISTRATION NUMBER N/A.